Pengembangan Produk Olahan Hasil Tangkap Perikanan Di Pulau Barrang Lompo - Abdullah, Akmal; Rusdi, Andi Rusdi Walinono; Ratna, Ratnawati; Budi, Budiman Haruna; Sulkifli (Hippocampus: Jurnal Pengabdian Kepada Masyarakat, 2022)
The potential of fish resources in coastal areas is very broad. but in general the people who live in coastal areas still live a life that is not prosperous. The low income of fishermen and fish cultivators is in stark contrast to the current fisheries potential and the competitive nature of the fishing business compared to other businesses. The purpose of this service is to increase the capacity of fisherwomen by practicing creating innovative fish and squid processed products and developing female fisherman's knowledge about business management. The method used includes the preparation stage, the next stage is production training and training on how to process fresh fish products. Selling points to produce attractive packaging for sale other than food preservative packaging. The conclusion of this community service as a whole the activities went well. This can be seen from the successful innovation of processed fishery products to help solve the problems of fisherwomen as processors of fishery products. as well as the total production capacity of female fishermen through training in the distribution of various processed fish products.